Judicial Overreach and the Rise of the Positive Legislator: A Constitutional Analysis of Indonesia’s Constitutional Court - Nur Faisyah; Muchamad Ali Safa'at; Riana Susmayanti (Правові горизонти, 2025)
The shifting role of the Constitutional Court from a negative to a positive legislator is not merely an expansion of authority; it also exhibits symptoms of judicial overreach that may threaten the principle of separation of powers. The Indonesian Constitutional Court was originally designed to function as a negative legislator, with the authority to review the constitutionality of laws without creating new legal norms. However, in practice, several Constitutional Court decisions have shifted toward a positive legislator role, wherein the Court engages in norm formulation as a form of judicial activism. This article aims to analyze the limits of such authority by examining three landmark decisions: Decision Numbers 102/PUU-VII/2009, 90/PUU-XXI/2023, and 62/PUU-XXII/2024. The analysis shows that the role of a positive legislator can be justified in urgent situations, particularly when a legal vacuum threatens to violate constitutional rights. Nevertheless, the Constitutional Court’s interventions must be limited, proportional, and free from conflicts of interest. This research proposes six substantive criteria as normative boundaries to ensure that the Court’s judicial activism remains within the constitutional framework and reinforces the system of checks and balances. These findings aim to strengthen the institutional design of constitutional justice in Indonesia.